Targeted Intracellular Delivery of Antibodies: The State of the Art - Slastnikova, Tatiana A.; Ulasov, A. V.; Rosenkranz, A. A.; Sobolev, A. S. (Frontiers in Pharmacology, 2018)
A dominant area of antibody research is the extension of the use of this mighty experimental and therapeutic tool for the specific detection of molecules for diagnostics, visualization, and activity blocking. Despite the ability to raise antibodies against different proteins, numerous applications of antibodies in basic research fields, clinical practice, and biotechnology are restricted to permeabilized cells or extracellular antigens, such as membrane or secreted proteins. With the exception of small groups of autoantibodies, natural antibodies to intracellular targets cannot be used within living cells. This excludes the scope of a major class of intracellular targets, including some infamous cancer-associated molecules. Some of these targets are still not druggable via small molecules because of large flat contact areas and the absence of deep hydrophobic pockets in which small molecules can insert and perturb their activity. Thus, the development of technologies for the targeted intracellular delivery of antibodies, their fragments, or antibody-like molecules is extremely important. Various strategies for intracellular targeting of antibodies via protein-transduction domains or their mimics, liposomes, polymer vesicles, and viral envelopes, are reviewed in this article. The pitfalls, challenges, and perspectives of these technologies are discussed.